A Comparative Immunohistochemical Study of Epithelial Membrane Antigen and NHERF1/EBP50 in the Diagnosis of Ependymomas. Issue 1 (January 2018) - Nambirajan, Aruna; Sharma, Mehar C.; Rajeshwari, Madhu; Kakkar, Aanchal; Suri, Vaishali; Sarkar, Chitra
Abstract : Ependymomas are gliomas that recapitulate normal ependymal cells. The epithelial membrane antigen (EMA) shows "dot-like" and "ring-like" staining patterns, highlighting "microlumens" or intracytoplasmic rosettes, a pathognomonic ultrastructural feature. NHERF1/EBP50, an adaptor protein localized at the apical plasma membrane of human epithelia, has been found to localize to these microlumens. We aimed to analyze the staining patterns of EMA and EBP50 in ependymomas and other tumors, and thereby compare their diagnostic utility. Sixty-three ependymomas of different grades and 44 nonependymal tumors (meningiomas, 5; pilocytic astrocytoma, 2; paraganglioma, 2; neurocytoma, 4; pituitary adenoma, 3; papillary tumor of pineal region, 3; oligodendroglioma, 4; choroid plexus papilloma, 3; medulloblastoma, 2; schwannoma, 2; cellular hemangioblastoma, 2; subependymal giant cell astrocytoma, 1; glioblastoma multiforme, 8; diffuse astrocytoma, 1; anaplastic astrocytoma, 1; and pilomyxoid astrocytoma, 1) were included. Ring-like positivity was 100% specific for ependymomas, but showed a poor sensitivity (EMA, 29%; EBP50, 37%). Dot EMA positivity was more sensitive in grade III ependymomas (100%), whereas dot EBP50 positivity was more sensitive in grade I subependymomas (80%) and myxopapillary ependymomas (40%). Among grade II ependymomas, EBP50 labeled a significantly higher number of dots and rings, which may be of value in small biopsies. Focal dot positivity for EMA and EBP50 in glioblastoma multiforme and meningioma contributed to the lowered specificity (EMA, 84%; EBP50, 80%). Myxopapillary ependymomas (60%), choroid plexus papillomas (66%), and papillary tumors of pineal region (100%) showed membranous staining with EBP50. Although EPB50 appears to be a better diagnostic marker for grade I/II ependymomas, we recommend a combined panel of EMA and EBP50 for grade III ependymomas to compensate for the reduced sensitivity of EBP50 in this subgroup.